2020
DOI: 10.1136/bmjopen-2020-037603
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of acupuncture for recurrent aphthous stomatitis: a systematic review protocol

Abstract: IntroductionRecurrent aphthous stomatitis (RAS) is a distressing symptom. There are many ways to treat RAS, such as pudilan anti-inflammatory oral liquid and doxycycline and laser therapy, but these take a long time to produce positive effects and compliance is low. Previous reviews of acupuncture treatment for RAS has been growing, but a systematic review is not available. To assess the efficacy and safety of acupuncture for the management of RAS.Methods and analysisThe following databases will be searched fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…Acupuncture, as an important part of complementary and alternative therapies, has numerous advantages, such as wide indication, reliable curative effect, convenient operation, economic safety, and has been widely accepted and applied worldwide [25]. Acupoints on the meridians are stimulated by using disposable sterile acupuncture needles [26]. A growing number of randomized controlled trials (RCT) have indicated that acupuncture could improve sleep quality, prolong sleep time, reduce the severity of insomnia disorder among the elderly [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Acupuncture, as an important part of complementary and alternative therapies, has numerous advantages, such as wide indication, reliable curative effect, convenient operation, economic safety, and has been widely accepted and applied worldwide [25]. Acupoints on the meridians are stimulated by using disposable sterile acupuncture needles [26]. A growing number of randomized controlled trials (RCT) have indicated that acupuncture could improve sleep quality, prolong sleep time, reduce the severity of insomnia disorder among the elderly [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the World Health Organization recommends acupuncture for the treatment of 16 inflammatory pain-related diseases, including rheumatoid arthritis (RA), acute gastritis, chronic gastritis, frozen shoulder, and allergic rhinitis ( WHO, 2013 ). Evidence shows that acupuncture can be a low-cost, low-risk therapy with few and minor adverse effects and it can help in the management of diseases involving inflammatory pain and reduce reliance on analgesics, including morphine ( Qin et al, 2016 ; Wu et al, 2018 ; A-Wang et al, 2020 ; Zhang et al, 2020a ). In patients with knee osteoarthritis (KOA), acupuncture can significantly relieve pain, attenuate the decline in physical function, and improve quality of life ( Corbett et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%